PENERAPAN METODE DESAIN TERPUSAT PENGGUNA PADA WEB SOSIAL UNSURYA CONNECT (STUDI KASUS : UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA) - Yoke Lucia Renica Rehatalanit; Maharani Yuliana Putri (Fakultas Ilmu Komputer dan Desain - Unsurya, 2020)
ABSTRACTAerospace University Marshal Suryadarma (Unsurya) is a University engaged in Technology and Social Affairs, given the importance of SWoT services within the University, researchers conduct research that has been devoted to IoT service requirements, along with the stages of service requirements: i). explore the factors that influence SwoT services at the University: making student decisions when using services, building perceptions and understanding of student relations with matters related to services. ii). check student real time interaction feedback when interacting with the initial SwoT and explore the needs of student interaction from services with in-depth interviews. iii). introducing conceptual and prototype implementations. iv). evaluate the SWoT service prototype with usability testing. The intended student contribution from this research is to provide an understanding of services when using the IoT system, and to inform the design of IoT services within the University. One way that will support the creation of the website is to use the PHP programming language. This website is designed using the Dreamweaver CS5 programming language with the help of the PHP-MySQL database and made in several stages, starting with the creation of a database, making navigation structures, displaying design and making programs. With the existence of Social Web, it is expected to help Students in accelerating access to the Unsurya Connect web.Â Keywords : Social Web of Things, Connect, Website, Internet.